(untitled) (Research, Society and Development, 2026)
This study aimed to perform a phytochemical screening of extracts from the leaves of Anacardium occidentale L. (cashew) and Anacardium microcarpum D. (cajui), based on the maceration of leaves using different solvents: distilled water, 70% ethanol, PA acetone, and PA hexane. The investigation sought to identify classes of secondary metabolites with therapeutic potential, such as alkaloids, flavonoids, tannins, and saponins, through specific qualitative tests. The use of solvents with varying polarities allowed for the evaluation of each solvent’s extraction efficiency in obtaining bioactive compounds. The results showed that the ethanolic extract presented the highest phytochemical diversity for both species, followed by aqueous and acetone extracts, while the hexane extract was the least efficient. Alkaloids were consistently present in all extracts, whereas flavonoids, tannins, and saponins varied depending on the solvent used. These findings reinforce the importance of solvent selection in phytochemical extraction and highlight the biotechnological and therapeutic potential of the studied species. Furthermore, the study contributes to the valorization of regional biodiversity and phytotherapy, offering a foundation for future research and the development of natural products for pharmaceutical application.